Analisis Kolokasi Leksikal dalam Tulisan Reflektif Mahasiswa Magister - Mia Dreina Antira Pujiningtyas; Barli Bram (Journal of Education and Teaching (JET), 2023)
The study aims to explore lexical collocations in master’s student reflective writings by classifying the collocations and figuring out the strengths of the word combinations using the Mutual Information (MI) scores. As a corpus-based study, the Corpus of Contemporary American English (COCA) was employed by the researchers. Therefore, the MI score of each lexical collocation could be carefully gathered and compared. The result of the study showed six types out of seven types of lexical collocations found in students’ reflective writings. Among the combinations, the noun and verb combinations were the most commonly found. The summarized data revealed that the number of word combinations with a stronger association was higher than the number of word combinations with a less significant association. Being get used to various English language inputs, the students were able to possess a wide range of lexical collocation repertoire and produce writings containing various word combinations with the significant association.